ANALISIS DAMPAK PEMBANGUNAN PASAR SENTRAL TERHADAP GUNA LAHAN PEMUKIMAN DI DISTRIK MIMIKA BARU KABUPATEN MIMIKA - junaed junaed; Risky Novan Ngutra; Thobby Wakarwamu (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2021)
The local government's policy in building the Central Market on Hasanuddin Street, Mimika Baru District, Mimika Regency which is integrated with the terminal has led to increased activity around the Central Market area which directly changes market economy actors such as traders/sellers, angkot drivers, motorcycle taxis and other service providers to centralize everything. activities and places to live in the area around the Market. For this reason, this study provides an overview of how to analyze the impact of the development of the central market on land use and analyze the spatial pattern of land use in Pasar Sentral sub-district so that it is expected to be able to overcome various challenges, namely the main problem, namely the tendency of spatial use that is not in accordance with the land use. To determine the development and use of residential land used secondary data in the form of maps with overlay techniques. The research uses a rationalistic approach with qualitative and comparative descriptive research methods. The trend of residential land use patterns and the factors that influence its growth.